Mistikus Cinta dalam Sejarah Gereja: Sebuah Apresiasi Kritis bagi Spiritualitas yang Dinamis - Paulus Dimas Prabowo (Journal Of Spirituality And Practical Theology, 2024)
Protestantism is considered a movement for the desacralization of Christianity which tends to prioritize doctrinal knowledge over spiritual experience. In fact, the Protestant Christian movement is seen as the fruit of the Enlightenment era. In fact, the aspect of affection or feeling does not have a place in this tradition, let alone spirituality and mysticism. The term 'mysticism' is even considered something evil. However, history seems to be filled with church mystics, some of whom influenced the thinking of the reformers. Those who understand the theology of mystical love are recorded as having a very deep experience of faith with God. This article seeks to provide a critical appreciation of the mysticism of love in church history and how this understanding contributes to the spirituality of Christians today. The method used is literature study, involving primary and secondary sources. The results show that some of the thoughts of the mystics of love can be applied today in the Protestant tradition, including Evangelicalism, and some cannot.